Evaluation of an online preoperative assessment tool. Issue 4 (29th June 2020) - O'Shea, John; Coleman, Margaret; Mahdy, Saad; Corbett, Mel; Curley, Ger
Abstract : Triaging patients into and away from preoperative assessment clinics remains a challenge. Anaesthesia Preoperative Assessment Tool (APAT) is a web application that delivers an online 22 question survey to patients at home, and uses an artificially intelligent algorithm to stratify patient risk and identify the need for non routine preoperative investigation and intervention. We assess APATs accuracy and patient acceptability in this prospective observational study. Patients were recruited at preoperative assessment clinic, where they were assessed by a consultant anaesthetist. Anaesthetist (ASA) grade, need for nonstandard investigation and intervention were recorded (gold standard). Patients were invited to complete an APAT assessment on their PC or smartphone at home, and the results of both assessments compared. 22 patients completed conventional clinical assessment by consultant anaesthetist and online assessment by APAT. APAT score correlates with clinicians ASA grade (rτ =0.6075, p=0.0008). APAT predicts patient risk group (misclassification rate of 0%, Area Under the Curve (AUC)=0.9825). APAT predicts the need for additional investigation (AUC=0.8077) and preoperative intervention (AUC=0.7193). Online assessment was acceptable to 92% of patients. Our findings support the hypothesis that APAT accurately predicts patients perioperative risk and predicts the need for investigation and intervention. Further studies are needed to confirm that APAT may be used to identify ASA 1 and 2 patients who could safely bypass preoperative assessment clinic.